Chemical characterisation and classification of forensic trace evidence - Maric, Mark (Curtin University, 2014)
Automotive paint, in the form of paint chips and/or smears, is one of the most commonly encountered forms of forensic trace evidence located at automotive related incidents. There is an increasing demand for more scientifically rigorous approaches to the interpretation of such evidence. This dissertation presents studies examining the use of a suite of spectroscopic techniques in conjunction with multivariate statistics, in order to develop analytical and interpretational protocols for automotive paint evidence.